Extending Signaling Theory to Rhetorical Signals: Evidence from Crowdfunding - Steigenberger, Norbert; Wilhelm, Hendrik (Organization Science, 2018)
Firms often need to acquire external financial resources to maintain and develop their business. To attract these resources, firms employ various substantive and rhetorical signals, such as publishing press releases, showcasing prototypes of new products, and hiring renowned managers. However, despite the relevance of signals, we still know little about how they interact—whether they strengthen, weaken, or neutralize one another—in attracting resources. Traditional signaling theory downplays the importance of rhetoric while management research acknowledges its relevance, creating a disconnect between these two camps and a shortcoming that deserves further investigation. To address this shortcoming, we advance the concept of signal portfolios. Signal portfolios may combine rhetorical signals with substantive signals. We employ this concept to explain how the interaction of the two affects financial resource acquisition in high-noise environments—settings where firms send multiple signals simultaneously. Based on longitudinal data on crowdfunding, an exemplary high-noise environment, we find that rhetorical signals complement substantive signals in certain situations and, thus, strengthen their impact on a firm’s financial resource acquisition. Contrary to our expectations, however, we find that under specific conditions, rhetorical signals may also weaken the impact of substantive signals. Our research has implications for signaling theory, crowdfunding research, and management practice. The online appendix is available at https://doi.org/10.1287/orsc.2017.1195 .